Keunggulan Penggunaan Fosfat Alam pada Pertanaman Kedelai di Lahan Kering Masam - Andy Wijanarko (Puslitbang Tanaman Pangan, 2015)
Phosphorus is an essential nutrient required in large quantities by plants after Nitrogen. Rock phosphate is an alternative to improve the P availability in the soil, especially in acid soils. The use of rock phosphate in agriculture, should primarily be initiated by improving its reactivity due to its low reactivity. Characteristics of rock phosphate, chemical and physical properties of soil, and type of crops grown are greatly affecting the direct application rock phosphate in agriculture. The natural phosphate may be improved by the application of organic matter, use of strong acid or sulfur, application of phosphate solvent microorganisms, and increase use of high solubility fertilizer such as SP-36.